Pemanfaatan Pekarangan Rumah Untuk Penunjang Ketahanan Pangan Masyarakat Desa Kayu Arang - Laksono, Aji; Fariadi, Herri (Universitas Dehasen Bengkulu, 2025)
This Thematic Community Service Program (KKN) aims to make use of home yards into chili farms to maintain community food security in Kayu Arang Village, Sukaraja District, Seluma Regency. The utilization of the yard is also designed to increase the consumption of a variety of local food sources with the principle of balanced nutrition. Food crop development can be directed by utilizing the potential that exists in the yard. National food security and independence can be achieved if it starts from the household. Integrated utilization of yard land is one of the technological innovations that can be used to realize food security, especially starting from the household. So that the outputs that want to be produced from this activity are scientific articles in the Journal of Community Service, videos of activities published on GoogleDrive and the Final Report in the form of a Report on the Results of the Implementation of UNIVED Thematic KKN Bengkulu Period 1. The methods used in Thematic KKN are participation, observation, interview, literature study and documentation.